COMPOSITION OF THE ICHTHYOFAUNA OF THE IGARAPÉ PRAQUIQUARA, CASTANHAL, EASTERN AMAZON - CHAGAS, Rafael Anaisce das (2019)
In the Amazon basin it is distributed the greatest diversity of freshwater fish in the world, but presents less than half of the species described and/or with little knowledge about its biology and distribution. This work presents the composition of the ichthyofauna Igarapé Praquiquara, located in the municipality of Castanhal, belonging to the Northeast Atlantic Hydrographic Region, Brazil, through collections were conducted in the years 2014 and 2015. A total number of 1,073 fish were sampled, belonging to five orders, 16 families, 35 genus and 42 species. Characiformes and Perciformes were the most predominant orders, Cichlidae and Characidae were the most abundant families, and Bryconops giacopinni, Cyphocharax gouldingi, Astyanax sp., Geophagus proximus and Satanoperca jurupari the most abundant species. Igarapé Praquiquara is composed of species with moderate commercial interest for commercial aquariums, with the presence of species cultivated in other regions. A structural analysis of the igarapé fish community is recommended in order to identify which factors are responsible for the composition of the ichthyofauna present, as well as the influence of the dam on the dispersion, distribution and reproduction of species.